DEVELOPMENT OF POWTOON AUDIO-VISUAL LEARNING MEDIA ON THE THEME OF MY HERO IN CLASS IV OF SD NEGERI SERANG 14 - Yayah Sunaiyah; Ujang Jamaludin; Reksa Adya Pribadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to develop PowToon audio-visual media on the theme of my hero and determine the teacher's involvement in the media, the response of students in using PowToon audio-visual media in learning, and determine the feasibility of the media developed. In this study using the development method or in English Research & Development, the research and development method is a research method used to produce certain products and test the effectiveness of these media (Sugiyono, 2016, p. 297). Based on the feasibility results that have been carried out by a team of media experts, material experts, and linguists. The results of research conducted by media experts obtained an average score of 89%, validation by material experts received an average score of 81%, and the results of linguist validation received an average score of 88%. The results of the student response questionnaire in the limited trial received a score of 93% and in the operational field trial received a score of 96%. This research shows that this research produces media products in the form of audio-visual PowToon on the theme of my hero. The percentage of feasibility results of media expert validation includes the